2022
DOI: 10.3389/fnagi.2022.998268
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in association between H-type hypertension and subcortical ischemic vascular disease

Abstract: BackgroundSubcortical ischemic vascular disease (SIVD) is a leading cause of vascular dementia. The present study tries to explore not only the gender-specific association between H-type hypertension and SIVD but also the indirect effects of H-type hypertension on cognition through the ischemic brain injury caused by SIVD.Materials and methodsA total of 601 SIVD patients were included, comprising 322 males and 279 females. H-type hypertension was defined as hypertension accompanied with elevated serum total ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Studies have reported that HHTN contributed to more cerebrovascular disease (CVD), such as stroke (8), and ultimately led to higher mortality (9,10). Compared with simple stroke patients, patients with both HHTN and stroke were reported to have a higher death rate and a greater potential for cognitive disorders (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that HHTN contributed to more cerebrovascular disease (CVD), such as stroke (8), and ultimately led to higher mortality (9,10). Compared with simple stroke patients, patients with both HHTN and stroke were reported to have a higher death rate and a greater potential for cognitive disorders (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that intestinal flora and blood uric acid levels are closely associated with Hcy. The elevation of plasma Hcy levels is mainly related to the following factors: 1) Nutritional factors: Hcy is negatively correlated with folic acid and 8) Vitamin B12 9) levels in the body; 2) Genetic factors: gene mutation, inherited methylation cycle abnormalities; 10) 3) Gender and age: Hcy is higher in males than in females and increases with age; 11) 4) Other: smoking, alcohol consumption, 12) lack of exercise, 13) psychiatric factors, etc. However, few of the above studies have been conducted with patients aged over 80 years, and their complex disease composition and physical status necessitate a unique prevalence mechanism analysis of H-type hypertension.…”
mentioning
confidence: 99%